The Role of Classroom Teachers in Supporting the Learning Process of Elementary School Students with Speech Delay - Anestya Diaz; Nur Matirda; Rodatul Hasanah; Suci Awwaliyah (Jurnal Wawasan Sarjana, 2025)
This study aims to describe and analyze the role of classroom teachers in supporting the learning process of children with special needs (CWSN) experiencing speech delay in an inclusive public elementary school. The background of this research is based on the importance of inclusive education and preliminary findings regarding the limited structural support available in the school. The research method employed was qualitative descriptive, with data collected through interviews, observations, and documentation. The findings reveal that classroom teachers play a crucial role by implementing personalized strategies, adaptive communication, and collaboration with parents, despite the absence of specialized learning systems or professional support such as special education assistants. Challenges encountered include a lack of professional training, the absence of an adaptive curriculum, and limited supporting facilities. This study emphasizes the pivotal role of classroom teachers as primary facilitators in bridging the needs of children with special needs and creating an inclusive learning environment. It also highlights the necessity of systemic support from educational institutions to ensure the effective implementation of inclusive practices.